Using discrete choice experiments to elicit palliative care preferences in lower middle-income countries: An exploratory study in Bhutan - Tara Devi Laabar; Richard Norman; Christobel Saunders; Mahbub Ul Alam; Ian W. Li (Palliative Care and Social Practice)
Background: Design and delivery of specific palliative care in many lower middle-income countries such as Bhutan remains limited. Designing care programmes to respond to the needs of patients and family networks is essential, but evidence on these preferences is limited. Aim: We have conducted a discrete choice experiment on Bhutanese patients and family members to explore preferences for palliative care. Design: The discrete choice experiment consisted of 15 choice tasks in which each respondent considered two competing palliative care services. Data were collected through the recruitment of respondents in conjunction with the clinician support teams, with data collected from both patients and their family members. All responses were pooled across the groups and analysed using the conditional logit regression model. Setting/participants: Fifty-seven respondents (20 patients and 37 family members) out of 98 (50 patients and 48 family members) identified (58.2%) were recruited through the three large referral hospitals in Bhutan. Patients had to be diagnosed with an advanced illness or at the end-of-life phase, but be able to understand and be willing to complete the survey. Similarly, family members had to be willing and able to complete the survey, and to be defined as the primary caregiver by the patient. Results: Transparent information provision, cost, family training and use of traditional healing practices were keen drivers of choice, with location of care and place of death relatively less important. Conclusion: Our results will guide future service design decisions in Bhutan and demonstrate the need for localised preference studies to enable culturally appropriate care including the provision of traditional healing practices.